Arecoline, Hesperidin and Trifluoperazine-mediated Cytotoxicity and Cell Death Potential in NIH/3T3 Fibroblasts Cells –Toxicity/Safety Assessment in a NIH/3T3 Model Fibroblast Cell Line - Varadharaj, Vembuli A; PK, Suresh (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim/Background: Arecoline is considered to be the principal etiologic agent for Oral Sub mucous Fibrosis (OSF) with the buccal fibroblasts being the major target. Hence, this model alkaloid has been used to evaluate toxicity and cell death potential in NIH/3T3 cells and compared with that of Hesperidin. Materials and Methods: Toxicity and cell death, for the two molecules, was tested using a battery of assays (MTT assay based cytotoxicity assessment; AO/EtBr assay-based determination of the percentage of dead cells; PI-based cell-cycle and cell death analysis using flow cytometry; DCFH-DA-based ROS levels). We also evaluated the role of S100A4 in this process using Trifluoperazine (TFP)- an antagonist of this protein. These experiments involved challenging the cells with arecoline and protecting them with Hesperidin and TFP separately. Results: IC50 measurements, based on the MTT assay, were found to be 38μM and 7. 5 Micromolar respectively. Based on the AO/EtBr and the flow cytometry assay, both the chemicals exhibited a dose-dependent increase in cell death. Both chemicals arrested the cells in different phases of the cell cycle. Arecoline and Hesperidin altered ROS levels in a dosedependent manner. Our challenge-protection experiments showed that Hesperidin and TFP, were able to reduce the arecoline-mediated cell death in NIH/3T3 fibroblasts. These results may due to an alteration in the ROS levels, despite quantitative differences in their cytotoxicity and cell death potential. The protection-challenge experiments showed that Arecoline and TFP may have a marginal cytoprotective effect. Conclusions: Our results substantiates and validates our experimental design to evaluate the toxicity and safety of model fibrotic chemicals as well as test the probable protective effects conferred by Hesperidin-like natural molecules as well as possibly address mechanistic issues pertaining to ROS as well as S100A4 antagonism using TFP and related molecules.
Keywords: Arecoline; Hesperidin; Trifluoperazine; S100A4; Cell Death; Protection-; Challenge; Challenge-Protection